Selected Plan Statistics 1982 Government of Bihar - Planning Commission (Planning Commission, 1982)
Devolution of taxes, Grants-in-aid and relief on repayment of Cen tral loans as per Seventh Finance Commission. Statewise distribution of Central loans Statement showing Revenue receipts and transfer from the Centre to total revenue —Bihar. Revenue receipts and transfer from the Centre to total revenue receipts for selected States, 1977-78. Growth of various taxes with respect to total State tax revenue Bihar.
Bihar State Planning Board Government of Bihar